Symbiotic Efficiency of Azide Resistant Mutants of Prosopis cineraria Rhizobia - Pancholy, Anjly (Annals of Arid Zone, 2016)
Seven rhizobial mutants, with enhanced resistance to sodium azide (25 ug ml-1 have been isolated following ultraviolet-irradiation of the native rhizobial strain, PC-1 (azide resistance 5 ug mf-1 of Prosopis cineraria. Five out of the seven isolated mutants (azi-l, azi-2, azi-4, azi-6, azi-7) showed significant increases in per cent shoot nitrogen (33-45%) and plant dry weight (14-40%) over the parent strain, PC-I. However, two isolated mutants. azi-3 and azi-5, did not show any improvement in nitrogen-fixing efficiency, in terms of per cent shoot N and plant dry weight possibly due to high reversion frequencies. It can be inferred that increased rhizobial resistance to azide and effectiveness are associated with each other in legume-Rhizobium symbiosis system.